A Systematic Literature Review of Self-Reported Smoking Cessation Counseling by Primary Care Physicians. - Anna-Lena Bartsch; Martin Härter; Jasmin Niedrich; Anna Levke Brütt; Angela Buchholz (PLoS ONE, 2016)
Tobacco consumption is a risk factor for chronic diseases and worldwide around six million people die from long-term exposure to first- or second-hand smoke annually. One effective approach to tobacco control is smoking cessation counseling by primary care physicians. However, research suggests that smoking cessation counseling is not sufficiently implemented in primary care. In order to understand and address the discrepancy between evidence and practice, an overview of counseling practices is needed. Therefore, the aim of this systematic literature review is to assess the frequency of smoking cessation counseling in primary care. Self-reported counseling behavior by physicians is categorized according to the 5A's strategy (ask, advise, assess, assist, arrange). An electronic database search was performed in Embase, Medline, PsycINFO, CINAHL and the Cochrane Library and overall, 3491 records were identified. After duplicates were removed, the title and abstracts of 2468 articles were screened for eligibility according to inclusion/exclusion criteria. The remaining 97 full-text articles reporting smoking cessation counseling by primary care physicians were assessed for eligibility. Eligible studies were those that measured physicians' self-reported smoking cessation counseling activities via questionnaire. Thirty-five articles were included in the final review (1 intervention and 34 cross-sectional studies). On average, behavior corresponding to the 5A's was reported by 65% of physicians for "Ask", 63% for "Advise", 36% for "Assess", 44% for "Assist", and 22% of physicians for "Arrange", although the measurement and reporting of each of these counseling practices varied across studies. Overall, the results indicate that the first strategies (ask, advise) were more frequently reported than the subsequent strategies (assess, assist, arrange). Moreover, there was considerable variation in the items used to assess counseling behaviour and developing a standardized instrument to assess the counseling strategies implemented in primary care would help to identify and address current gaps in practice.